IMPLEMENTASI KEGIATAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DALAM MENINGKATKAN BIG FIVE PERSONALITY SISWA DI SDN 59/IV KOTA JAMBI - Putri Rizkia, Nadila; Hariandi, Ahmad; Faisal Hidayat, Akhmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education in Indonesia aims to produce a generation that is intelligent and has character according to Pancasila values. This research examines the implementation of the Pancasila Student Profile Strengthening Project (P5) in developing the Big Five Personality dimensions in fifth grade students at SDN 59/IV Jambi City. With a qualitative approach, the results show that P5 supports openness, collaboration, responsibility and managing students' emotions, while strengthening Pancasila values ​​such as tolerance and diversity. This research confirms the importance of project-based learning innovation for adaptive and effective character education.